2008
DOI: 10.4049/jimmunol.180.4.2634
|View full text |Cite
|
Sign up to set email alerts
|

Notch3 Inhibition in Myelin-Reactive T Cells Down-Regulates Protein Kinase Cθ and Attenuates Experimental Autoimmune Encephalomyelitis

Abstract: Among its varied functions, Notch signaling is involved in peripheral T cells responses. The activation and polarization of CD4+ T cells toward a Th1 lineage are essential steps in the pathogenesis of multiple sclerosis and its animal model, experimental autoimmune encephalomyelitis. Inhibition of all four Notch receptors with a γ-secretase inhibitor was shown to block Th1-type polarization and to attenuate the symptoms of experimental autoimmune encephalomyelitis. In this study, we have examined the role of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 35 publications
5
73
1
Order By: Relevance
“…Recent studies have drawn direct correlations between specific Notch receptors and IL-17 production in autoimmunity. 38 We here demonstrated that inhibition of Notch signaling by DAPT significantly decreased the secretion of IL-17 in dose-dependent manner in ITP patients. The inactivation of Notch signaling may disrupt IL-17 production, and IL-17 production might be dependent on the Notch signaling in ITP.…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies have drawn direct correlations between specific Notch receptors and IL-17 production in autoimmunity. 38 We here demonstrated that inhibition of Notch signaling by DAPT significantly decreased the secretion of IL-17 in dose-dependent manner in ITP patients. The inactivation of Notch signaling may disrupt IL-17 production, and IL-17 production might be dependent on the Notch signaling in ITP.…”
Section: Discussionmentioning
confidence: 90%
“…In a model of passively transferred EAE, the adoptive transfer of lymph node cells treated with Notch 3-specific neutralizing antibodies, but not with Notch 1-specific neutralizing antibodies, reduced the release of IFNγ and IL-17 by myelin-reactive cells, with a corresponding decrease in the EAE disease scores 75 . Of note, it was not possible to determine in this study whether the lower levels of IFNγ produced resulted from impaired T H 1 cell differentiation and/or from impaired T H 1 cell function.…”
Section: The Impact Of Notch On T H 1 Cell Function In Vivomentioning
confidence: 99%
“…This inflammation-mediated demyelination disease of the central nervous system (CNS) can be induced by immunization with myelin antigens, viral infection or transfer of autoreactive T cells. Genetic and pharmacological interference with Notch signalling, as well as administration of blocking antibodies against Notch receptors or Delta-like ligand 4 (DLL4), impeded progression of the disease, resulting in reduced clinical severity 74,75,84,91,92,[118][119] . The mechanisms by which blockage of Notch signalling ameliorates EAE are not fully understood and require further investigation.…”
Section: Box 2 | Notch and Autoimmune Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies against Notch receptors can be used to regulate Notch signaling. Some antibodies have been already developed against Notch1 and Notch3 receptors (Asano N., et al 2008, Elyaman W., et al 2007, Jurynczyk M., et al 2008, Maekawa Y., et al 2003, Schaller MA., et al 2007and Li K., et al 2008. Antibodies can block specific Notch receptors with a high selectivity, leaving other Notch receptors activated.…”
Section: Endogenous Inhibitorsmentioning
confidence: 99%